Modelo de maturidade e auditoria da gestão da inovação em micro, pequenas e médias empresas (SMES) brasileiras - Mafra Pereira, Frederico Cesar (2019)
Objective: To analyze the degree of innovation management and propose a maturity model for Brazilian SMEs. Methodology/Approach: Comparative study cases of quantitative and qualitative approach, descriptive and applied, for Brazilian SMEs; used the deductive and inductive methods and the triangulation of data for analysis and proposition of the model. Originality/Relevance: The challenge of understanding in depth the critical factors and relationships between innovation, performance and competitiveness of SMEs is important for their survival, growth and development, especially in emerging economies such as Brazil. Main Results: (i) despite the practical difficulties of managing innovation and the absence of a formal strategy in some SMEs to encourage and support innovative processes, these are directly and indirectly related to the performance and competitiveness of these companies; (ii) the degree of innovation maturity is influenced by the characteristics of SMEs and their managers. Auditing and management of innovation increase their capacity for survival, growth and business development. Theoretical / Methodological contributions: (i) theoretical, by collaborating to fill the aforementioned gap and broaden the knowledge on the subject within the scope of SMEs; (ii) applied, by proposing a specific framework for auditing and measuring the degree of maturity of innovation in SMEs, based on a validated framework in the international literature. Social / Management contributions: The proposed model brings managerial contributions by refining the praxis of SMEs in innovation management, offering companies in similar situations an opportunity for competitive benchmarking.